"This does my head in". Ethnographic study of self-management by people with diabetes - Hinder, S; Greenhalgh, P (BioMed Central, 2012)
Background Self-management is rarely studied ‘in the wild’. We sought to produce a richer understanding of how people live with diabetes and why self-management is challenging for some. Method Ethnographic study supplemented with background documents on social context. We studied a socioeconomically and ethnically diverse UK population. We sampled 30 people with diabetes (15 type 1, 15 type 2) by snowballing from patient groups, community contacts and NHS clinics. Participants (aged 5-88, from a range of ethnic and socio-economic groups) were shadowed at home and in the community for 2-4 periods of several hours (total 88 visits, 230 hours); interviewed (sometimes with a family member or carer) about their self-management efforts and support needs; and taken out for a meal. Detailed field notes were made and annotated. Data analysis was informed by structuration theory, which assumes that individuals’ actions and choices depend on their dispositions and capabilities, which in turn are shaped and constrained (though not entirely determined) by wider social structures. Results Self-management comprised both practical and cognitive tasks (e.g. self-monitoring, menu planning, medication adjustment) and socio-emotional ones (e.g. coping with illness, managing relatives’ input, negotiating access to services or resources). Self-management was hard work, and was enabled or constrained by economic, material and socio-cultural conditions within the family, workplace and community. Some people managed their diabetes skilfully and flexibly, drawing on personal capabilities, family and social networks and the healthcare system. For others, capacity to self-manage (including overcoming economic and socio-cultural constraints) was limited by co-morbidity, cognitive ability, psychological factors (e.g. under-confidence, denial) and social capital. The consequences of self-management efforts strongly influenced people’s capacity and motivation to continue them Conclusion Self-management of diabetes is physically, intellectually, emotionally and socially demanding. Nonengagement with self-management may make sense in the context of low personal resources (e.g. health literacy, resilience) and overwhelming personal, family and social circumstances. Success of self-management as a policy solution will be affected by interacting influences at three levels: [a] at micro level by individuals’ dispositions and capabilities; [b] at meso level by roles, relationships and material conditions within the family and in the workplace, school and healthcare organisation; and [c] at macro level by prevailing economic conditions, cultural norms and expectations, and the underpinning logic of the healthcare system. We propose that the research agenda on living with diabetes be extended and the political economy of self-management systematically studied.